Interplay between programmed death-ligand 1 and non-coding RNAs - Ghafouri-Fard, Soudeh; Shoorei, Hamed; Hussen, Bashdar Mahmud; Poornajaf, Yadollah; Taheri, Mohammad; Sharifi, Guive (Frontiers in Immunology, 2022)
Programmed death-ligand 1 (PD-L1) is a transmembrane protein with essential roles in suppression of adaptive immune responses. As an immune checkpoint molecule, PD-L1 can be exploited by cancer cells so as to evade the anti-tumor attacks initiated by immune system. Thus, blockade of PD1/PD-L1 axis can eliminate the suppressive signals and release the antitumor immune responses. Identification of the underlying mechanisms of modulation of activity of PD1/PD-L1 axis would facilitate design of more efficacious therapeutic options and better assignment of patients for each option. Recent studies have confirmed the interactions between miRNAs/lncRNAs/circRNAs and PD1/PD-L1 axis. In the current review, we give a summary of interactions between these transcripts and PD-L1 in the context of cancer. We also overview the consequences of these interactions in determination of response of patients to anti-cancer drugs.